2015
DOI: 10.1007/s13277-015-3090-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-10b and minichromosome maintenance complex component 5 gene as prognostic biomarkers in breast cancer

Abstract: The aim of this study is to identify micro-ribonucleic acid (microRNA) and its target, in addition to their relationship to the outcome in breast cancer (BC). To achieve this aim, we investigated microRNA-10b (miR-10b) and minichromosome maintenance complex component 5 (MCM5 mRNA) expression in 230 breast tissue samples by real-time PCR and semiquantitative conventional RT-PCR, respectively. Relapse-free survival (RFS) associated with miRNA-10b and MCM5 mRNA were tested by Kaplan-Meier survival analysis. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…miR-10b overexpression was associated with poor prognosis in breast cancer37 and gliomas 38. In colon cancer, miR-10b showed increasing expression in higher stage disease 39.…”
Section: Discussionmentioning
confidence: 97%
“…miR-10b overexpression was associated with poor prognosis in breast cancer37 and gliomas 38. In colon cancer, miR-10b showed increasing expression in higher stage disease 39.…”
Section: Discussionmentioning
confidence: 97%
“…Zhao et al [26] demonstrated that miR-221 may be a predictive biomarker for BC. In the research of Eissa et al [27], patients with BC positive for miR-10b had shorter relapse-free survival rates, and miR-10b was an independent prognostic factor of BC. MiR-451 influenced the drug resistances and miR-129-5p regulated radiosensitivity via accelerating the apoptosis of breast cancer cells [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The association between the overexpression of MCMs with the clinicopathological factors and progression in various types of cancers has been confirmed in several studies (9)(10)(11)(12)(13)(14)(15). However, there are few studies that have investigated the expression levels of MCM5 and their relationship with the clinicopathological factors in tumours (13)(14)(15)(16)(17).…”
mentioning
confidence: 83%